JUDGE'S PERSPECTIVE ON THE CONCEPT OF JUSTICE IN DIVORCE FOR CIVIL SERVANTS - Dumaria Evi Mawartiku Palamarta Br. Gultom; Rosnidar Sembiring; Yefrizawati Yefrizawati; Afnila Afnila (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
The reason Judges give decisions for civil servants who get divorced without superiors' permission is because the principle function of court decisions is to protect in realizing social justice for all Indonesian people, trials are carried out for the sake of justice based on belief in one and only God, the principle of independence of judges, that judicial power is state power. which is independent, the principle of the court may not refuse cases, the judge is obliged to explore, follow and understand the value of law and the sense of justice that lives in society. Divorce perpetrators, both those with Civil Servant and Non-Civil Servant status, are expected to really understand and know the implications (legal consequences) for violations, in the form of not fulfilling the requirements and procedural divorce, for example for Civil Servants who will divorce and do not attach permission from his superiors